2008
DOI: 10.1089/end.2007.9838
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Ureteroureterostomy: Description of Technique

Abstract: RALU is a reliable and efficient technique for the correction of ureteral obstruction in children and can be applied to any pathology that requires ureteral reconstruction, regardless if it is a duplicated or a single system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 14 publications
(19 reference statements)
0
21
0
2
Order By: Relevance
“…Passerotti et al have reported that RAUU for the correction of ureteral obstruction in children is a reliable and efficient technique, and can be applied to any pathology that requires ureteral reconstruction, regardless if it is a duplicated or a single system (26).…”
Section: Outcomementioning
confidence: 99%
“…Passerotti et al have reported that RAUU for the correction of ureteral obstruction in children is a reliable and efficient technique, and can be applied to any pathology that requires ureteral reconstruction, regardless if it is a duplicated or a single system (26).…”
Section: Outcomementioning
confidence: 99%
“…Its first use for in a child was reported in 2001, when Meininger et al [11] performed a Nissen fundoplication in a 10-year-old girl. Since then, it has been applied for pediatric urologic [12][13][14][15], cardiac [16,17], hepatobiliary [18,19], diaphragmatic [20,21], thoracic [22,23], and anti-reflux procedures [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the main traditional surgical options available include balloon dilatation ( ± cautery), endoureterotomy (cold knife, diathermy or laser), open surgical repair, and lastly nephrectomy if the renal unit is symptomatic and not functioning. More recently, formal repair of ureteric injuries using 'minimally invasive' laparoscopic or robotic techniques have been described [1]. However, these latter superspecialized solutions are not applicable/ available to the wider UK general population.…”
Section: Discussionmentioning
confidence: 99%